2020
DOI: 10.1177/0300060520903656
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and lifestyle-related factors as predictors for health-related quality of life among early adolescents: a cross-sectional study

Abstract: To examine whether lifestyle-related factors and resilience predict health-related quality of life (HRQoL) in a sample of early adolescents. Methods: A total of 611 eighth grade pupils (response rate: 79%) participated in this crosssectional study. The variables measured were physical activity (accelerometer), cardiorespiratory fitness (Andersen test) and a questionnaire assessing dietary habits, sleep disturbance, resilience (Resilience Scale for Adolescents) and HRQoL (KIDSCREEN-27). Results: A total of 36% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…One important aspect of QoL is the socioeconomic status (income, o education) of individuals, which is an important variable that should be sideration when assessing the resilience during a specific shocking event the presence of infectious diseases [18,19]. For instance, households in Ch Several studies have been carried out to investigate the mediating role of resilience in the relationship between negative factors and different aspects of an individual's well-being [12,13]. For instance, indicators of psychological illness like depression and anxiety are associated with poor resilience [14], whereas the absence of psychological illness is known to be correlated to a higher level of resilience [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important aspect of QoL is the socioeconomic status (income, o education) of individuals, which is an important variable that should be sideration when assessing the resilience during a specific shocking event the presence of infectious diseases [18,19]. For instance, households in Ch Several studies have been carried out to investigate the mediating role of resilience in the relationship between negative factors and different aspects of an individual's well-being [12,13]. For instance, indicators of psychological illness like depression and anxiety are associated with poor resilience [14], whereas the absence of psychological illness is known to be correlated to a higher level of resilience [15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, indicators of psychological illness like depression and anxiety are associated with poor resilience [14], whereas the absence of psychological illness is known to be correlated to a higher level of resilience [15]. Furthermore, the relationship between resilience and QoL in a stressful environments or a fatal disease had previously been proven [10,12]. Published studies have shown that, resilience impacts QoL in certain populations with some diseases such as cancer [16], multiple sclerosis [10] and Parkinson's disease [17] amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO has recognized the key dimensions of general health and well‐being as being physical, psychological, and social well‐being and functioning as per the multidimensional Health‐Related Quality of Life (HRQoL) construct (Bottolfs et al, 2020). There is limited research available examining HRQoL among young people.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited research available examining HRQoL among young people. A Norwegian study of 611 Year 8 students reported that resilience was a positive predictor of HRQoL ( β , 0.18–0.27), providing a protective factor against the risk of disease and enabling positive outcomes for adolescents (Bottolfs et al, 2020). An earlier study of 1100 Norwegian adolescents reported moderately strong relationships between resilience and physical health, where higher scores of resilience factors were associated with structured, well‐organized, and frequent physical activity (Moljord et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the choice of variables assessed within them suggested a predominantly psycho-social model. Although research has linked resilience to well-being and QoL (e.g., Bottolfs et al, 2020 ), it is not known whether this model is “universal.” Such information could be valuable to vulnerable cultures and also to policy-makers seeking to prepare local communities for disaster, e.g., from climate change or pandemic. The availability of international data and methods offers an opportunity for original research.…”
Section: Introductionmentioning
confidence: 99%